Tackling the World's Fastest-Growing HIV Epidemic : More Efficient HIV Responses in Eastern Europe and Central Asia - Zhao, Feng (Washington, DC: World Bank, 2020)
The Eastern Europe and Central Asia region has the world’s fastest growing HIV epidemic. Although still concentrated, the epidemic has diversified, affecting several key populations in many countries. This change has increased the number of people in need, the ways the epidemic can spread, and the complexity of formulating an effective strategy to combat it. At the same time, international funding is insufficient to cover the growing need, and domestic plans to cover the funding gaps, in many cases, fall short. In this environment, the need to use data to make the best possible decisions about using available funds is essential. Tackling the World’s Fastest-Growing HIV Epidemic tells the story of how, in 11 countries across Eastern Europe and Central Asia, small groups of decision-makers and experts came together to carry out innovative, groundbreaking analyses for each country. It details the steps these nations have taken to strengthen their HIV programs based on the findings while highlighting critical issues for the road ahead. In so doing, the book also shows the potential of what can be done with a mathematical model and how it can support real-life improvements in policy and more efficacious budget allocations. It is the record of a unique undertaking to improve public health investments that offers lessons for many communities.